Breastfeeding in women affected by systemic lupus erythematosus: Rate, duration and associated factors. (May 2021) - Orefice, Valeria; Ceccarelli, Fulvia; Pirone, Carmelo; Galoppi, Paola; Spinelli, Francesca Romana; Alessandri, Cristiano; Brunelli, Roberto; Perrone, Giuseppina; Conti, Fabrizio
Objective: Breastfeeding is a crucial moment for both mothers and child, providing a beneficial effect on child survival, nutrition, development and on maternal health. Despite the prevalent involvement of childbearing women in systemic lupus erythematosus (SLE), breastfeeding is still a neglected topic. The objective of this study was to evaluate breastfeeding frequency, duration and associated factors in SLE women. Methods: We consecutively enrolled SLE pregnant women reporting demographic, clinical, serological, gynaecological and obstetric data. Breastfeeding experience was evaluated by using a specific questionnaire. Disease activity was assessed before and during pregnancy as well as during postpartum. Results: A total of 57 pregnancies in 43 SLE women were included in the present study. In almost all the pregnancies, mothers planned to breastfeed their child (96.5%) and forty-one (71.9%) actually did breastfeed. The median time of breastfeeding was 3 months (IQR 7). Non-breastfeeding women showed a more frequent caesarean section (p = 0.0001), IUGR occurrence (p = 0.004) and disease relapse (p = 0.0001) after pregnancy. When comparing patients according with breastfeeding duration (cut-off 6 months), we found a significant more frequent smoking habitus (p = 0.02), caesarean section (p = 0.009), and joint involvement during postpartum (p = 0.0001) in women breastfeeding for less than or equal to 6 months, together with higher median BMI (p = 0.0001). Moreover, breastfeeding duration was positively associated with disease duration and hydroxychloroquine (HCQ) treatment during disease history, pregnancy and postpartum. Conclusions: SLE women didn't show lower breastfeeding rate in comparison with general population but they presented higher prevalence of early discontinuation within three months. Early interruption was positively associated with smoking, BMI, joint involvement; meanwhile disease duration and HCQ treatment during postpartum were positively associated with a longer breastfeeding duration.